Pengaruh Kerja Fleksibel, Berbagi Pengetahuan, dan Kepercayaan Terhadap Kinerja dan Komitmen Organisasional - Cuwanditha, I Putu Dava; Darma, Gede Sri (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The aim of current study is to investigate key determinants that can enhance job performance within all LPDs operating in the Kuta District area. The research targets a population of 200 employees across all LPDs within Kuta District. Utilizing census sampling, all 200 employees were included as research respondents. Empirical data was gathered through a questionnaire employing a 10-point Likert scale, which was subsequently analyzed using the Structural Equation Modeling (SEM) approach with SmartPLS software. The findings of this research indicate that optimal performance can be achieved when organizations, particularly LPDs, afford their employees freedom and flexibility in managing their time and workspace, foster active interaction and collaboration in knowledge sharing among employees, exhibit high levels of employee commitment to the organization, and establish trust among internal LPD parties. Notably, the study reveals that organizational commitment can serve as a significant moderating factor. This research contributes positively to the human resources literature by presenting a research framework that incorporates organizational commitment as a moderating variable. Moreover, it offers practical implications for LPDs in formulating strategies or approaches that can effectively create and enhance employee job performance.